Not Now! Now! Chronopolitics, Art & Research - Lorenz, Renate (Publication Series of the Academy of Fine Arts Vienna, 2014)
In her divergent and interdisciplinary book Not Now! Now! Chronopolitics, Art & Research Lorenz illuminates the topic of chronopolitics through contributions from art theorists, artists, and artistic researchers. With a foreword by Elizabeth Freeman, whose work has delved extensively on such notions as temporality and body politics, Lorenz invites the reader to explore postcolonial and queer debates through artistic practices that foreground time.In the introduction, Lorenz locates her interest in the numerous intersections between deferral, opacity, and respect talking about "chrononormativity", "respectability", "straight time", and the right not to be clearly seen/read as a defense against aggression. She analyses Kenneth Anger's film "Puce Moment", and later Oliver Husain's "Purfled Promises" in order to discuss further on É. Glissant's concept of opacity encompassing at once otherness - or a sense of a-synchronicity with the norm - in terms of race and queerness.